Peningkatan Hasil Belajar Menggunakan Metode Pembelajaran Mind Mapping - Upik Elita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The research aims at describing the process and learning achievement through mind mapping method. The research was an action research begun with : a) planning, b) action and observation , c) reflection. The process of the research was classified into two cycles. The subject was class XI MIPA 5 consist of 32 students with 15 orang males and 17 females. The data were collected through test, observation, interview and documentation. The data analysis was conducted both qualitatively and quantitatively. The result showed the improvement of students' achievement after treated with mind mapping method. Before treatment, the percentage was 46,77% which improved to 70,39 % after the First cycle and improved to 82.22% after the second cycle. In conclusion, there was an improvement of biology learning achievement by applying mind mapping method. Keywords: mind maping method, achievement